History of Geology:: Early Work in Quaternary Botany in Canada - Warner, Barry (Geoscience Canada, 1986)
Summary The first collections of Quaternary fossil plants in Canada were made by Sir William Dawson in 1857. His collections were probably the first in North America and among the first in the world. Noteworthy contributions by D.P. Penhallow laid the foundation of Quaternary botany in Canada with his studies on the fossils from the famous Sangamonian Don Formation at Toronto and late Wisconsinan nodules at Green Creek, Ottawa, in addition to numerous miscellaneous collections from across Canada. A re-examination of these early collections and new samples from some of the same localities reveals a high standard of identification and interpretation. Interestingly, current Canadian Quaternary botanists have no links with the early pioneers; they came here during the 1950's from European and American lineages.